Implicancias del Decreto Legislativo 1425 en la determinación del pago a cuenta del impuesto a la renta de la empresa Inversiones y Negociaciones Pilares, ejercicio 2019 - Córdova Gutiérrez, Huber (2019)
The present investigation is of the utmost importance, because it allows us to analyze the modification of the Income Tax Law on the accrual criteria to determine the tax implications for the application of Legislative Decree N° 1425 in the calculation of Payment on account of the Tax to the Income of the company Inversiones y Negociaciones Pilares S.A.C. for the year 2019. The research was carried out using the descriptive method and analytical method; The development was achieved with the use of a survey aimed at the administrative and accounting area in order to obtain information on the tax situation of the company. To achieve the objectives of this work, it was determined; the situational status of the treatment of the accrual principle in determining the payment on account of the income tax, the tax situation as of the year 2019 and the documents to take into account for the support of the determination of the payment on account of the tax to the rent. After analyzing and interpreting the information obtained, it was determined that the company has not been carrying out adequate control for the transfer of assets, which influences the determination of the tax base for the calculation of payments on account of Income Tax. Therefore, an erroneous application of article 57 of the Income Tax Law, given the amendment introduced by Legislative Decree No. 1425, will result in a pecuniary penalty or fine which will have an impact on the economic and financial situation of the company. for the commission of the infraction typified in article 178 of the Tax Code.